Chronic endometritis-causing bacteria in Arabic mares - Babak Qasemi- Panahi; Milad Khodaii; Gholamali Moghaddam; seyyed abbas Rafat (The Iranian Journal of Veterinary Science and Technology, 2022)
Bacterial infections of the uterus are known to be an important cause of infertility in the mare. The objective of this study was to determine the species of bacteria isolated from the uterus of infertile Arabic mares, and investigate how identified bacteria are related to parity. A total of 18 Arabic mares with a history of long-term infertility were evaluated. The age range of mares was 4-23 years. For statistical analysis, logistic regression and Chi-square test were used by Proc Logistic of SAS. In this study, low-volume uterine flush and culture techniques were used. P. aeruginosa was the most prevalent bacterium isolated from 26.32% of mares as pure or in conjunction with E. coli, K. pneumoniae, or Citrobacter spp. Furthermore, 23.68% of bacterial infertility cases were related to E. coli. Pure growth of E. coli was observed only in one case. However, mixed growth with P. aeruginosa, S.zooepidemicus, and S. aureus was very prevalent. The present study revealed that the most prevalent bacteria isolated from chronic endometritis in Arabic mares were gram-negative bacteria (p < 0.05), while in some cases may be accompanied by gram-positive bacteria. C. albicans was isolated in only 8% of mares with chronic endometritis. Moreover, older age and higher parity number of the mares were not related to the presence of intrauterine fluid or the species of bacteria (p > 0.05). It can be concluded that the most prevalent bacteria isolated from infertile Arabic mares with chronic endometritis are gram-negative bacteria.